2015
DOI: 10.1021/acs.biochem.5b01074
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Investigation of Novel Nitric Oxide (NO)-Releasing Prodrugs as Drug Candidates for the Treatment of Ischemic Disorders: Insights into NO-Releasing Prodrug Biotransformation and Hemoglobin–NO Biochemistry

Abstract: We have developed novel NO-releasing prodrugs of efaproxiral (RSR13) for their potential therapeutic applications in a variety of diseases with underlying ischemia. RSR13 is an allosteric effector of hemoglobin (Hb) that decreases the protein’s affinity for oxygen, thereby increasing tissue oxygenation. NO in the form of ester prodrugs has been found useful in managing several cardiovascular diseases by increasing blood flow and oxygenation in ischemic tissues, due to its vasodilatory property. We synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…Crystallographic studies with the prodrugs showed RSR-13, the hydrolysis product of the prodrugs bound to the central water cavity of deoxygenated Hb (as described above) that explained these compounds ability to decrease Hb affinity for oxygen (Xu et al 2015). Moreover, the released NO, was observed exclusively bound to the two α hemes, which was suggested to be due to RSR-13 decreasing the protein's affinity for the ligand at the β hemes (Xu et al 2015).…”
Section: Exogenous Modulatorsmentioning
confidence: 82%
See 1 more Smart Citation
“…Crystallographic studies with the prodrugs showed RSR-13, the hydrolysis product of the prodrugs bound to the central water cavity of deoxygenated Hb (as described above) that explained these compounds ability to decrease Hb affinity for oxygen (Xu et al 2015). Moreover, the released NO, was observed exclusively bound to the two α hemes, which was suggested to be due to RSR-13 decreasing the protein's affinity for the ligand at the β hemes (Xu et al 2015).…”
Section: Exogenous Modulatorsmentioning
confidence: 82%
“…Safo's group recently developed novel nitric oxide (NO)-releasing prodrugs of RSR-13 derivatives by attaching the NO-releasing moieties nitrooxyethyl, nitrooxypropyl, and 1-(pyrrolidin-1-yl)diazen-1-ium-1,2-diolate, respectively, to the carboxylate of RSR-13 (Xu et al 2015). Crystallographic studies with the prodrugs showed RSR-13, the hydrolysis product of the prodrugs bound to the central water cavity of deoxygenated Hb (as described above) that explained these compounds ability to decrease Hb affinity for oxygen (Xu et al 2015). Moreover, the released NO, was observed exclusively bound to the two α hemes, which was suggested to be due to RSR-13 decreasing the protein's affinity for the ligand at the β hemes (Xu et al 2015).…”
Section: Exogenous Modulatorsmentioning
confidence: 99%
“…The Brookhaven protein databank (PDB) was also consulted for ligands bearing a nitrate ester. While merely four such structures were found (3k2f, 3ni5, 4fr8, and 5e29), in two of these the nitrate ester’s N atom is in close contact with an electron rich atom. In 4fr8 (Figure a) the tris-nitrate ligand TNG-601 is buried within an aromatic-rich pocket and one of the nitrate N atoms is in close contact (2.89 Å) with a S atom from the disordered cysteine 302.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is notable that these compounds are stable in DMSO at room temperature for extended periods of time, suggesting that the NO release is facilitated in the whole blood. The mechanism of biotransformation of the nitrate esters to release NO has been proposed to involve both an enzymatic action and a chemical hydrolysis [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%